Proactive versus reactive corporate environmental practices and environmental performance - Kim, Kyungho (Sustainability (Switzerland), 2018)
This study investigates how different types of corporate environmental practices affect environmental performance. This paper is theoretically anchored in the natural resource-based view and, methodologically, it applies the recently recommended disaggregated approach in a new effort to deepen our understanding of how environmental performance is associated with different types of corporate environmental practices. The results partially affirm the argument of the natural resource-based view that proactive corporate environmental practice leads to better environmental performance, whereas reactive corporate environmental practice is associated with worse environmental performance. However, the relationship between corporate environmental practices and environmental performance should be carefully interpreted, because the findings differ depending on how Kinder Lydenberg Domini (KLD) strength and concern rating scores are measured. The results further demonstrate that the disaggregate KLD environmental rating scores can be better alternative measures for corporate environmental practices than the commonly used composite and aggregate KLD rating scores, given that disaggregate KLD concern and strength scores represent independent rather than similar constructs. The findings are expected to help both theorists and practitioners achieve a more nuanced understanding of the measurement of environmental practices.
Keywords: Environmental performance; Environmental practices; Kinder Lydenberg Domini; Toxic releases